Science education and the english second language learner - Morris, Judith (Curtin University, 2006)
The growing diversity of school populations around the world means that for many students the language of instruction in mainstream classrooms is not their first language. Content-based second language learning in a context such as a science classroom is considered advantageous as it enables the learner to manipulate a target language such as English in a way which is meaningful. However, science students who have yet to achieve communicative competence in English are disadvantaged when it comes to developing a deep understanding of scientific concepts. Many mainstream science teachers have concerns about this significant group of learners who can be left on the periphery of the class to cope as best as they can. Very often teachers aim to meet the needs of English Second Language (ESL) learners without any specific knowledge of the strategies which would enhance learning and ensure that learning environments encourage participation and interaction. The students themselves have not only to deal with language and sociocultural issues but must face the cognitive demands of science including negotiating its specialised language.The study had two main purposes. The first goal was to describe the current situation with respect to nine ESL learners of science and their teachers in selected learning environments in Australia. The secondary purpose was to bring about improvement in the students' situations by employing specifically designed interventions. The study had three focal areas: the language; the teaching and learning environment; and the ESL student. It was conducted in three phases. Phase one involved investigating the current situations in the three focal areas. Phase two involved reflection, planning and development of the broad interventions and specific strategies which were used to assist teaching and learning. In phase three the strategies were implemented and their effectiveness was analysed using a multidimensional interpretive framework. Changes in communicative competence, interactional and participative competencies and academic competence were observed. The interventions which were intended to promote communicative competence for the language focus, involved integration of language and literacy instruction with science education. To improve participation and interaction in the teaching and learning environment, individual assistance was provided. In order to promote academic competence for the students, content, process and/or product modifications were made to science courses.Data for the qualitative case studies was collected using classroom observation, teacher and student interviews, checklists of strategies and language errors, and portfolios of student work. Observations of the science classes in phase one revealed that, even for the students with very limited English language proficiency there was little ESL specialist support available. Mainstream subjects like science provided opportunities for language development, with biology lessons consistently including more activities which involved a combination of speaking, listening, reading and writing than did chemistry or physics classes. However, there was no coordinated approach to integrating language education with science education. The development of cognitive1 academic language took longer than 10 years for some of the students in the study. The non-technical language used in science lessons affected the students' understanding much more than the teachers were aware. Teachers' attitudes and beliefs strongly influenced the interaction and participation of ESL students in science classrooms. Developing language skills prevented ESL students asking and answering questions in class and academic progress in science was impeded by limited opportunities for ESL students to clarify their understanding. Achievement in science was affected by assessment instruments which were infused with specific linguistic or cultural knowledge.After the introduction of the interventions, improvements in communicative competence occurred for all students with the greatest progression occurring in the students with less developed language skills. Interaction and participation improved markedly in the science classrooms where teachers provided individual assistance to students. Academic competence increased in all cases. The most promising approaches included: addressing the specific language needs in a particular unit of work; the development of customized materials; the provision of weekly tutorials; and the revision of assignment drafts.